2006
DOI: 10.1103/physrevd.74.034017
|View full text |Cite
|
Sign up to set email alerts
|

Diquark Bose-Einstein condensation

Abstract: Bose-Einstein condensation (BEC) of composite diquarks in quark matter (the color superconductor phase) is discussed using the quasi-chemical equilibrium theory at a relatively low density region near the deconfinement phase transition, where dynamical quark-pair fluctuations are assumed to be described as bosonic degrees of freedom (diquarks). A general formulation is given for the diquark formation and particle-antiparticle pair-creation processes in the relativistic flamework, and some interesting propertie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
2
21
0
Order By: Relevance
“…Also a typical diquark coupling which is usually adopted in the literature of color superconductivities [33,34] is located well below the unitary point. Based on these points, we have concluded that the following "exotic" conditions are required to have the diquark BEC [55,58] in quark matter core in compact stars; (i) the attraction between quarks is much larger than expected perturbatively [102], and (ii) the in-medium fermion mass is larger than the perturbative hard dense loop calculation [103] and must be comparable to chemical potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a typical diquark coupling which is usually adopted in the literature of color superconductivities [33,34] is located well below the unitary point. Based on these points, we have concluded that the following "exotic" conditions are required to have the diquark BEC [55,58] in quark matter core in compact stars; (i) the attraction between quarks is much larger than expected perturbatively [102], and (ii) the in-medium fermion mass is larger than the perturbative hard dense loop calculation [103] and must be comparable to chemical potential.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the existence of the RBEC phase has been confirmed at T = 0 in the Leggett's flamework and the evolution of collective modes are reported [56]. Investigation of such a relativistic crossover is also performed in a boson-fermion model [58,59] which together with a chemical equilibrium condition enables us to describe the crossover thermodynamics with a boson mass or chemical potential controlled by hand. A possible importance of the diquark BEC in QCD phase diagram at low density is demonstrated in a model calculation [60].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the non-Abelian nature of QCD, various realizations are expected in the vacuum itself with finite temperature and density, called ''QCD phase diagram.'' Up to now, interesting phase structures are proposed by using some low-energy effective theories of QCD, e.g., a confined phase with mesons and baryons, a deconfined phase with quark-gluon plasma (QGP), a chiral symmetry broken phase with mass generation [16], color superconductivity as diquark condensation [17][18][19][20][21], etc. In fact, some wisdom about QGP gives the insight for the early universe just after the big bang [22].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the stronginteraction nature of quantum chromodynamics (QCD), quark matter at moderate densities is a typical example of a relativistic many-fermion system where a departure from the BCS-like behavior is to be expected. The early work in this respect focused on the structural change of Cooper pairs at strong coupling and precursor phenomena above the critical temperature for the superconducting phase transition, in particular the appearance of the pseudogap in the spectrum [28,29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%